1996
DOI: 10.1074/jbc.271.7.3541
|View full text |Cite
|
Sign up to set email alerts
|

Different Fate of a Single Reporter Protein Containing KDEL or KKXX Targeting Signals Stably Expressed in Mammalian Cells

Abstract: In mammalian cells, resident luminal and type I transmembrane proteins of the endoplasmic reticulum usually contain KDEL and KKXX at the carboxyl terminus. These sequences induce retrieval from compartments located downstream in the secretory pathway. It has been suggested that the retrieval may occur from multiple sites, ranging from the intermediate compartment to the trans-Golgi network. To compare the retrieval of luminal and type I membrane proteins, we have used different forms of a single reporter, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…Although CD4-TM1E and CD4-TM1prM were localized in the ER at steady state, our data do not exclude transport to the cis Golgi followed by recycling to the ER, as observed for luminal proteins containing a C-terminal sequence of the prototype KDEL (Lewis & Pelham, 1992;Martire et al, 1996;Townsley et al, 1993). To answer this question, cells expressing CD4-TM1E or CD4-TM1prM were treated with nocodazole.…”
Section: Localization Signals In Tm1 Of E and Prm Induce A Static Retmentioning
confidence: 95%
“…Although CD4-TM1E and CD4-TM1prM were localized in the ER at steady state, our data do not exclude transport to the cis Golgi followed by recycling to the ER, as observed for luminal proteins containing a C-terminal sequence of the prototype KDEL (Lewis & Pelham, 1992;Martire et al, 1996;Townsley et al, 1993). To answer this question, cells expressing CD4-TM1E or CD4-TM1prM were treated with nocodazole.…”
Section: Localization Signals In Tm1 Of E and Prm Induce A Static Retmentioning
confidence: 95%
“…This motif has been identified to be a retrieval motif that brings proteins from an unknown sorting compartment back to the ER (Jackson et al, 1990). It is shown that the KKXX-mediated retrieval can occur at several sites between the intermediate compartment and the trans-Golgi network (Jackson et al, 1993;Martire et al, 1996). COOHterminal dilysine-motifs bind specifically to the protein complex coatomer Letourneur et al, 1994;Lowe and Kreis, 1995), which is essential for the retrieval of dilysine-tagged proteins to the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies-The following antibodies were used: the OKT8 mouse anti-CD8 monoclonal antibody, from Ortho (Raritan, NJ), the N1 mouse anti-CD8 monoclonal antibody (29), a rabbit anti-ERGIC-53 antibody (30), a rabbit anti-GM130 antibody, a rabbit anti-Sec31 antibody, and a rabbit anti-giantin antibody (31), a mouse anti-hemagglutinin antibody, and a rabbit antihemagglutinin antibody from Santa Cruz. The anti-GRASP65 polyclonal antibody was obtained through immunization against a fusion protein between glutathione S-transferase (GST) and rat GRASP65 and affinity purified; the anti-GRASP55 polyclonal antibody was a kind gift of Dr. F. Barr.…”
Section: Methodsmentioning
confidence: 99%